Mahathir & skandal Perwaja - Badaruddin Ismail ([Bukit Beruntung, Selangor Darul Ehsan: Noor Abadi Enterprise, 2003)
On the alleged involvement of Mahathir bin Mohamad in the Perwaja scandal, a Malaysian state-owned steel company.
Cover title.
In Malay.
Keywords: Mahathir bin Mohamad, -- 1925-; Scandals -- Malaysia; Malaysia -- Politics and government